Manajemen Kepala Madrasah Dalam Meningkatkan Mutu Madrasah di MTs Negeri Gresik - Pamuji (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This research aims to answer questions regarding the formulation of the problem: first, about how the management of madrasa heads improves the quality of madrasas; secondly, about what are the supporting and inhibiting factors for madrasa head management in improving the quality of madrasas. This type of research includes qualitative research, which produces data and analysis using descriptive methods adapted to field studies. Data collected used observation, interview and documentation techniques. The results of this research can be said that there are four stages in madrasa head management, namely: Planning, Organizing, Actuating, and Controlling. Implementation of madrasah head management in Planning is holding coordination meetings with the academic community (madrasah heads, vice-principals, teachers and staff). In organizing, tasks and responsibilities are divided into each division. Actuating the implementation of quality improvement programs from the results of meetings that have been mutually agreed upon, and the head of the madrasah providing direction. And the last one is the controlling stage, this is carried out by monitoring Job Descriptions and evaluations at meetings at the beginning and end of the school year. Supporting factors include young and superior, creative and innovative human resources, fairly complete facilities, strategic location and effective learning. Meanwhile, inhibiting factors include a lack of funds to complete existing infrastructure.